Predictors of Diabetic Foot Ulcer Recurrence: A Retrospective Analysis of Clinical, Vascular, and Biochemical Risk Factors - Ruangsak, Chanika; Thi Lan, Nguyen; Minh Huyen, Tran; Fujimoto, Haruka (Global Indonesia Health Care (GOICARE), 2025)
Background: Diabetic foot ulcer (DFU) is a major complication of diabetes mellitus and remains a significant contributor to morbidity, limb amputation, and mortality. Although substantial efforts have been made in prevention and treatment, ulcer recurrence continues to pose a critical clinical challenge. Understanding the multifactorial nature of recurrence and identifying reliable predictors are essential for improving long-term outcomes. Methods: This retrospective case-control study included 230 patients diagnosed with DFU and treated between October 2020 and January 2025. Patients were stratified into recurrence (n = 103) and non-recurrence (n = 127) groups based on ulcer outcomes within a two-year follow-up period. Clinical, demographic, foot-related, comorbid, and biochemical variables were extracted from medical records and follow-up assessments. Statistical analyses included univariate tests and binary logistic regression to determine independent predictors of DFU recurrence. Results: Significant differences were found between groups across multiple domains. Patients with recurrence had lower body mass index (BMI, p = 0.045) and a higher prevalence of poor financial status (p = 0.021). Foot-specific characteristics, including higher Wagner grade, prolonged ulcer duration, prior amputations, and plantar ulcer location, were all significantly associated with recurrence (p < 0.05). Laboratory findings revealed elevated C-reactive protein and decreased serum albumin levels in the recurrence group (p < 0.001). Notably, lower total bilirubin (TBIL) levels were observed in recurrent cases and remained an independent protective factor (OR = 0.898, p = 0.041). Multivariate analysis identified diabetic peripheral neuropathy (DPN), peripheral arterial disease (PAD), prior amputations, and plantar ulceration as significant predictors of recurrence. Conclusion: DFU recurrence is driven by a complex interplay of vascular, neurological, anatomical, and biochemical factors. The identification of total bilirubin as a potential protective biomarker highlights new avenues for risk stratification. These findings underscore the importance of a comprehensive, multidisciplinary approach in DFU management to reduce recurrence and improve patient outcomes.